Media Sosial dan Komunikasi Politik: Isu Utang sebagai Komunikasi Politik di Masa Pemilihan Umum 2024 - Saksono, Eko Hari; Putranto, Algooth (Magister of Communication Science, Sahid University Jakarta., 2023)
The research utilized qualitative data analysis for its data. This is intended to provide a more comprehensive understanding of problems encountered during data collection that directly or indirectly correlates to the research, its environment, subjects, or others. According to Miles and Huberman, data analysis consists of three activities that occur simultaneously. Based on the research, we discovered that communication behavior coming from the use of social media, with a focus only on Twitter, is diverse. In other words, Twitter can help provide information related to the subjects’ social interaction, perspective, and views of on certain social issues and conditions as they post their opinions and thoughts onto the Twitter channels to interact with other users who identify as their online friends or followers. The growth of the internet and the fast-changing culture make social media a staple of the current community to communicate, especially in today’s modern society. In this research, it was found that Government Public Relations failed to respond to the speed of communication on social media using the issue of state debt